Emotional intelligence and emotion information processing: Proof of concept of a test measuring accuracy in discriminating emotions - Christelle Gillioz; Maroussia Nicolet-dit-Félix; Oliver Wilhelm; Marina Fiori (Frontiers in Psychology, 2023)
Emotion information processing (EIP) has been recently introduced as a new component of emotional intelligence. We present a task aiming at measuring a type of emotion information processing related to fine-grained discrimination of emotional expressions. We modified an existing task presenting morphed faces created from a blend of two prototypical emotional expressions. Participants’ (N = 154) ability-EI, in particular emotion recognition, understanding and management, as well as intelligence were evaluated. Results show that all facets of EI independently predicted accuracy in the discrimination task and that emotion recognition was the strongest predictor. When controlling for emotion recognition level, we found that emotion understanding still predicted accuracy for less difficult stimuli. Results support the idea that individuals high in EI have higher emotion processing skills at the emotion perception stage of information processing and suggest that the task employed in the current study might measure more spontaneous processing of emotional expressions. Implications regarding the use of the current task as a new measure of the EIP component are discussed.